Identification and Analysis of Stress-Associated Protein (SAP) Transcription Factor Family Members in Pinus massoniana - Yulu Zhao; Xingyue Ren; Jingjing Zhang; Wenya Yu; Qiong Yu; Kongshu Ji (Plants)
Stress-associated proteins (SAPs), belonging to the A20/AN1 zinc finger protein family, are key regulators in plant stress responses. Despite their importance, studies on the SAP gene family in Pinus massoniana are still relatively scarce. This study aimed to systematically identify and characterize SAP genes in P. massoniana and to explore their potential roles in stress response mechanisms. A total of 17 PmSAP genes were identified from P. massoniana. Phylogenetic analysis revealed that these genes group into five distinct clades, and 10 conserved motifs were identified. Using transcriptome data and qRT-PCR, we analyzed their expression patterns and employed yeast systems to validate their transcriptional activities. The responses of PmSAP gene family members to different stress treatments showed significant differences. For example, PmSAP8 and PmSAP12 responded strongly to ABA, MeJA, and H2O2 treatments, while PmSAP3 and PmSAP5 showed significant upregulation under ETH and NaCl stress. Yeast experiments indicated that PmSAP6/8/12 were transcriptional activators, and PmSAP3 and PmSAP5 were transcriptional suppressors. The identification and preliminary analysis of PmSAP genes provided a theoretical foundation for understanding stress resistance mechanisms in P. massoniana.